Insulin resistance and metabolic syndrome criteria in lean, normoglycemic college-age subjects. Issue 5 (September 2018) - Townsend, Dana K.; McGregor, Katheryn; Wu, Esther; Cialkowski, Kathryn; Haub, Mark D.; Barstow, Thomas J.
Abstract: Aims: The goal of this study was to determine insulin sensitivity in a fasted state and during an oral glucose tolerance test (OGTT), in normoglycemic (NGT), lean (L) (n = 35) and, for comparison, overweight/obese (OW/O) (n = 9) college-aged subjects. Materials and Methods: Insulin sensitivity for 44 NGT, normotensive subjects, age 18–26 yrs., was determined by homeostasis model assessment (HOMA-IR) and from Matsuda index (ISI Matsuda). Results: Subjects were normoglycemic fasted (4.59 +  0.35 mmol/L) and at two hours post OGTT (4.52  +  1.35 mmol/L). Besides anthropometric measures, there were significant differences between OW/O and L for fasting insulin ( P  < 0.001) and both measures of insulin sensitivity ( P  < 0.05). All subjects exhibited a 9-fold range in HOMA-IR (0.88 +  0.51, range 0.3–2.7) and an 8-fold range in ISI Matsuda (11.9 +  4.7, range 3.0–24.2). The latter was inversely correlated with systolic blood pressure ( r  = 0.35, P  = 0.04) even though subjects were normotensive. In lean subjects, 2.3% were IR by HOMA-IR >  2.1, 5.7% by ISI Matsuda <  5.9, and 22.9% had > one criteria for metabolic syndrome (MetS); 28.6% had some negative metabolic biomarker. Conclusions: Insulin resistance is present in lean, NGT college-age subjects even without MetS criteria and is discernable with an easily applicable OGTT-derived index.